2021
DOI: 10.1021/acschemneuro.1c00210
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 Inhibits Aβ Fibrillation and Disaggregates Preformed Fibrils in the Presence of Synthetic Neuronal Membranes

Abstract: The aggregation of amyloid β (Aβ) peptide with subsequent formation of fibrils which deposit in senile plaques is considered one of the key triggers of Alzheimer's disease (AD). Molecules targeting the inhibition of Aβ fibrillation and/or the disruption of Aβ fibrils are thus promising approaches for the medical prevention and treatment of AD. However, amyloid formation is a complex process strongly influenced by the cellular environment, such as cell membranes, which may affect the effectiveness of therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…It has been shown that vitamin B12 reduces amyloid pathology by different mechanisms. These include the decreased gene expression of BACE1 and PS1 [ 135 , 136 , 137 , 138 ], two important enzymes for the release of Aβ peptides out of APP [ 139 , 140 , 141 , 142 ]; decreased cholesterol de novo synthesis [ 143 ]; and the inhibition of Aβ fibrillization and aggregation [ 128 , 144 ]. The protective effect of vitamin B12 in respect to tau hyperphosphorylation and tau aggregation is reported to be caused by an elevation in the activity of the phospholipase A2 [ 145 ], an inhibition of kinases involved in tau phosphorylation e.g., GSK-3β [ 146 ], and by the direct binding of vitamin B12 to tau proteins [ 147 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that vitamin B12 reduces amyloid pathology by different mechanisms. These include the decreased gene expression of BACE1 and PS1 [ 135 , 136 , 137 , 138 ], two important enzymes for the release of Aβ peptides out of APP [ 139 , 140 , 141 , 142 ]; decreased cholesterol de novo synthesis [ 143 ]; and the inhibition of Aβ fibrillization and aggregation [ 128 , 144 ]. The protective effect of vitamin B12 in respect to tau hyperphosphorylation and tau aggregation is reported to be caused by an elevation in the activity of the phospholipase A2 [ 145 ], an inhibition of kinases involved in tau phosphorylation e.g., GSK-3β [ 146 ], and by the direct binding of vitamin B12 to tau proteins [ 147 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study (2021), the inhibitory effect of vitamin B12 on Aβ fibrillation could be shown by the use of artificial neuronal membranes mimicked by liposomes as Aβ generation is strongly influenced by the lipid environment of cellular membranes. To mimic neuronal cell membranes, lipid components at comparable ratios were chosen to compose the lipid vesicle: phosphatidylcholines (1,2-dimyristol-sn-glycero-3-phosphocholine), cholesterol, sphingomyelin and phosphatidylserine (L-α-phosphatidylserine) [ 153 ]. Performing a ThT fluorescent assay in the presence of Aβ1–42 and presence or absence of vitamin B12 the authors found that vitamin B12 slows down the transition from Aβ oligomers to mature fibrils and significantly reduced the content of fibrils in aqueous solution without the synthetic neuronal membranes.…”
Section: Vitamin B12 Cell Culture and Animal Studies Related To The Molecular Mechanisms Of Ad And Ad Pathologymentioning
confidence: 99%
“…Cationic liposomes were also produced by the thin-film hydration method followed by extrusion [38]. DOTAP and CHOL (molar ratio 85:15) were dissolved in chloroform, and a thin lipid film was obtained after the evaporation of the organic solvent under a nitrogen stream.…”
Section: Preparation Of Liposomesmentioning
confidence: 99%